Analisa kapasitas infiltrasi tanah pada lahan pertanian dan lokasi rencana tapak bangunan menggunakan metode horton - Erna Kusuma Wati (UNIVERSITAS INDRAPRASTA PGRI, 2019)
It has been done measurement of infiltration capacity on agricultural land in the National University Laboratory and the land plans of building sites in Grahayana, Karawang Barat. Analysis of the infiltration capacity data using the Horton equation model. Measuring the infiltration capacity of the field using a double infiltrometer ring and immersed into the ground. The water advance observation is measured in 5-minute intervals. Measurements were repeated for five days on each land use. The results of the research showed that the average value on agricultural land is relatively slow, which is 6.24 cm/h and on the Land plan site is relatively slow, namely at 5.41 cm/h.